ANALISIS PENURUNAN BANGUNAN REVETMENT DENGAN PERKUATAN STRUKTUR CERUCUK MATRAS BAMBU PADA TANAH LUNAK DENGAN METODE ELEMEN HINGGA DAN INSTRUMENTASI LAPANGAN - Umar Alfaruqi Abdurrahman; Wiwik Rahayu; Fathiyah Hakim Sagitaningrum; Putera Agung Maha Agung (LPPM Universitas Abdurrab, 2024)
Soft soil is one type of soil that often causes problems if proper planning is not carried out. An alternative method to improve the bearing capacity of soft soil is by utilizing bamboo materials as piles and mattress in the foundation of a building structure. Bamboo material is chosen because of its advantages such as abundance, affordability, short harvesting period, environmental friendly, and buoyancy optimization. In this study, a comparison of settlement was conducted between finite element method and field instrumentation observations on a wharf structure along the Kapuas River in Pontianak, which utilizes bamboo mattress piles as soil reinforcement. The soil deposit at the site is predominantly soft soil up to 28 m for the thickness with shallow groundwater levels. Stability and settlement analyses were performed using finite element method utilizing Plaxis software. The construction of the revetment structure was done gradually following observations from instrumentation. In the numerical analysis, the soil layers were modeled as Mohr-Coulomb materials. Bamboo piles were modeled as elastic-plastic springs, while bamboo mattress were modeled as elastic beams. From the instrumentation observations and numerical analysis, it was found that the revetment structure with bamboo pile and mattress provided stability against sliding and failure of bearing capacity. Thus, it can be concluded that the use of bamboo as piles and mattresses for reinforcing soft soil can be carried out and provides additional support for soft soil.